2019
DOI: 10.3233/jbr-190383
|View full text |Cite
|
Sign up to set email alerts
|

Antagonistic effects of phenolic extracts of Chokeberry pomace on E. coli O157: H7 but not on probiotic and normal bacterial flora

Abstract: BACKGROUND: Enterohemorrhagic Escherichia coli (EHEC) is still a major foodborne bacterial infectious agent in the USA and causes both diarrheal disease and hemolytic uremic syndrome (HUS). As antibiotic therapy is not an option, appropriate antimicrobial or inhibitor against EHEC colonization/infections is urgently needed. OBJECTIVE: Develop an appropriate natural antimicrobial and stimulate host defense to control foodborne illnesses with EHEC. METHOD: We investigated the role of chokeberry (Aronia melanocar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Previously, we also reported that CFCS CLA impaired physicochemical properties of bacterial pathogens such as autoaggregation, surface hydrophobicity, and biofilm formation of several enteric bacterial pathogens more efficiently than CFCS wt (Vu et al, 2009;Peng et al, 2018;Tabashsum et al, 2018). As the physicochemical properties play a major role in pathogenic bacterial adherence to host cells, secretion of effector proteins, and initiate colonization (Sorroche et al, 2012;Cordonnier et al, 2017;Aditya et al, 2019), we also compared the expression of genes which are involved in such physicochemical properties and secretion of proteins in the presence of CFCSs collected from LC wt and LC CLA . Major virulence genes involved in EHEC Type-III secretion system (T3SS), i.e., eaeA, espA espB, espD, tir, and ler are downregulated presumably by the polyunsaturated fatty acid components of CFCSs (Cardenal-Muñoz and Ramos-Morales, 2011;Peng and Biswas, 2017;Peng et al, 2018).…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…Previously, we also reported that CFCS CLA impaired physicochemical properties of bacterial pathogens such as autoaggregation, surface hydrophobicity, and biofilm formation of several enteric bacterial pathogens more efficiently than CFCS wt (Vu et al, 2009;Peng et al, 2018;Tabashsum et al, 2018). As the physicochemical properties play a major role in pathogenic bacterial adherence to host cells, secretion of effector proteins, and initiate colonization (Sorroche et al, 2012;Cordonnier et al, 2017;Aditya et al, 2019), we also compared the expression of genes which are involved in such physicochemical properties and secretion of proteins in the presence of CFCSs collected from LC wt and LC CLA . Major virulence genes involved in EHEC Type-III secretion system (T3SS), i.e., eaeA, espA espB, espD, tir, and ler are downregulated presumably by the polyunsaturated fatty acid components of CFCSs (Cardenal-Muñoz and Ramos-Morales, 2011;Peng and Biswas, 2017;Peng et al, 2018).…”
Section: Discussionmentioning
confidence: 91%
“…The effect of the collected metabolites against EHEC EDL933 growth was determined quantitatively in vitro following the method previously described in triplicate (Peng et al, 2015a;Salaheen et al, 2016;Aditya et al, 2019). Briefly, individual culture tubes containing LB broth and one of the CFCSs (CFCS wt , CFCS wt+PF , or CFCS CLA ) in a ratio of 3:1 (v/v) was used as a treatment, where the same ratio of LB and MRS broth was considered as control.…”
Section: Assay Of Ehec Edl933 Inhibition With Cfcss Collected From Lcmentioning
confidence: 99%
See 2 more Smart Citations